2021
DOI: 10.1101/2021.02.02.429358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of tumour microenvironment remodelling following oncogene inhibition in preclinical studies with imaging mass cytometry

Abstract: Mouse models are critical in pre-clinical studies of cancer therapy, allowing dissection of mechanisms through chemical and genetic manipulations that are not feasible in the clinical setting. In studies of the tumour microenvironment (TME), novel highly multiplexed imaging methods can provide a rich source of information. However, the application of such technologies in mouse tissues is still in its infancy. Here we present a workflow for studying the TME using imaging mass cytometry with a panel of 27 antib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, similarly to other targeted therapies, early clinical results indicate that drug resistance frequently arises, resulting in clinical relapses (11,12). KRAS G12C inhibitors not only affect the survival of cancer cells but can also mediate immunomodulatory effects by reversing KRAS-driven immunosuppressive mechanisms and generate a TME that is more favorable for an anti-tumour immune response (8,19,21). This knowledge has served as a rationale to investigate clinical combinations of KRAS G12C inhibitors with anti-PD1 or PD-L1 antibodies (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, similarly to other targeted therapies, early clinical results indicate that drug resistance frequently arises, resulting in clinical relapses (11,12). KRAS G12C inhibitors not only affect the survival of cancer cells but can also mediate immunomodulatory effects by reversing KRAS-driven immunosuppressive mechanisms and generate a TME that is more favorable for an anti-tumour immune response (8,19,21). This knowledge has served as a rationale to investigate clinical combinations of KRAS G12C inhibitors with anti-PD1 or PD-L1 antibodies (29).…”
Section: Discussionmentioning
confidence: 99%
“…KRAS inhibition in consequence leads to an increased sensitivity of tumour cells to type I and II IFNs, which translates to higher expression of IFN-induced genes such as T cell chemoattractants and antigen presentation genes that could positively affect anti-tumour immunity in vivo. Using Imaging Mass Cytometry (IMC) we recently showed that there was an inclusion of macrophages and neutrophils in the core of 3LL DNRAS lung tumours, while effector cells remained at the tumour periphery (21). Consistent with this apparent immunosuppressive TME, growth of these tumours was not affected by a lack of B and T cells in Rag1 showed that migration was significantly abrogated when bone marrow-derived monocytes were cultured in conditioned medium from MRTX-treated cells and to a similar extent when cultured in medium from Ccl2 -/cells (Fig 4H).…”
Section: Kras G12c Inhibition Enhances Tumour Cell Intrinsic Ifn Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence for the potential of KRAS-G12C inhibition to reduce the immunosuppressive tumour microenvironment produced by oncogenic KRAS and potentially sensitise tumours to immune checkpoint blockade came from another study using the 3LL ∆NRAS murine lung carcinoma line [118]. Using imaging mass cytometry, significant changes in tumour immune contexture induced by KRAS inhibition were clearly evident.…”
Section: Combination Of Kras Inhibition With Immunotherapymentioning
confidence: 99%